Space Management for Children - Kitsahawong, Kemporn; Kitsahawong, Somsak (Khon Kaen University Dental Journal, 2020)
There are several causes of early loss of primary teeth. Consequences of early loss of primary teeth are imbalance of force to adjacent teeth, which may lead to undesirable tooth movements and create space shortage in the dental arch. Space deficiency can provide detrimental effects on the developing permanent dentition or increase the severity of malocclusions with crowding. Therefore, using an intra-oral space maintainer to preserve arch length following the premature loss of primary teeth/tooth is crucial. To ensure proper treatment in individual patient, appropriate treatment planning and designing the right appliance are very important and need to consider the relevant factors. This article aims to provide detailed information about the causes and factors affecting the loss of space due to premature loss of primary teeth, including guidelines for examination and treatment planning for appropriately manage individual patient. In addition, to deliver information about the considerations for the use of space maintainers and how to maintain the space in the dental arch. The advantages, disadvantages and limitations of different kind of appliances were discussed in order to assist on decision making for selecting appropriately appliances in patients.